Student Teacher Engagement in Co-Teaching Strategies - Stobaugh, Rebecca; Everson, Kimberlee (Educational (Re)naissance, 2020)
Recently there has been increasing emphasis on co-teaching experiences for teacher candidates. Despite the significance of collaboration between cooperating teachers and student teachers, limited empirical attention has focused on student teachers' co-teaching experiences. The following study utilized survey data to ascertain if student teachers' use of different co-teaching strategies changed over the course of their student teaching semester, as well as, compared student teacher use of co-teaching strategies in elementary, middle, and secondary program areas. Pilot Study Survey data revealed that approximately one-fourth of the student teacher's time is spent teaching alone. However, the Student Teacher Survey data indicated that the Team Teaching co-teaching strategy increased more than any other co-teaching strategy in all program areas. The study concludes that as teacher education programs seek to maximize the benefits of the co-teaching model, student teachers and cooperating teachers need additional training in ways to utilize all the co-teaching strategies to maximize student learning.